SOScessory blueprint / Adlan Khairulfazi, Siti Nur Sakinah Ahmad Maliki … [et al.] - KHAIRULFAZI, ADLAN; AHMAD MALIKI, SITI NUR SAKINAH; MOHD ZAIN, NUR ZULAIKHA; NASIR, FAEZUL KAMIL (2018)
SOScessory is a safety device disguised as a versatile accessory, in the sense it can beworn as earrings, bracelet or button badge according to the user's preferences. This safetydevice acts an SOS tracker device, signaling help and the user's exact location toemergency contacts in times of distress. It also features a defense tool mechanism and anapplication system to best utilise the device. SOScessory is small in size and disguised asa versatile accessory to serve the purpose of not being detected by potential aggressors.